Peningkatan Kemampuan Problem Solving dalam Matematika melalui Model Problem-Based Learning di MI Negeri 3 Halmahera Utara - Kasmir , Nurlaela (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Problem solving skills in mathematics are essential for students to face academic challenges and everyday life. However, students at MIN 3 North Halmahera still experience difficulties in solving mathematics problems that require problem solving. One of the reasons is the less interactive learning method, where teachers still use the lecture method a lot so that students become passive. This study aims to analyse the effectiveness of the Problem-Based Learning (PBL) model in improving students’ problem solving skills. The method used is Classroom Action Research (PTK) with two cycles, involving observation, interviews, questionnaires, and formative tests. The results showed that the PBL model had a positive impact on students’ ability to understand problems and develop solutions systematically. In the second cycle, students became more active, confident, and better able to work in groups. In addition to improving problem solving skills, the PBL model also increased students’ learning motivation. However, there were obstacles such as different levels of student participation and a longer time allocation. Therefore, additional strategies are needed to make the implementation of this model more effective.